Communication, media and social movements in Chile, a balance of (a quarter of a) century - Saavedra , Jorge (Comunicación y Medios, 2023)
This article presents a detailed summary of media and communications research on social movements in Chile during the 21st century. In recent decades, this field has received significant interest in areas that this study groups around the representation of causes, subjects, and the future of movements by the media; their performative character in urban space; the counter-informative and participatory/organisational role of social networks; and, finally, the ontological character of media and communication in contexts of demonstration and protest. After reviewing 70 works from academic articles, book chapters, and books, the paper provides a detailed look at the main paths that shape the field of communication and media studies on social movements and invites us to observe the gaps and challenges it presents for the coming years.